PENATAAN KEMBALI LEMBAGA EKSEKUTIF: STUDI KOMPARATIF ANTARA INDONESIA DAN AMERIKA SERIKAT BERDASARKAN PRINSIP CHECKS AND BALANCES - Erga Yuhandra; I. Gde Pantja Astawa; Iman Jalaludin Rifa’i (Universitas Kristen Satya Wacana, 2025)
Executive institutional restructuring is a crucial issue in constitutional law because it determines governmental effectiveness, institutional certainty, and the balance of power. This study analyses executive institutional arrangements in Indonesia and the United States and compares the application of the checks and balances principle in executive restructuring. It employs normative legal research with a comparative legal approach, analysing legislation, legal doctrines, and scholarly literature. The findings show that Indonesia grants the President broad authority to establish, modify, and dissolve executive institutions, whereas the United States designates Congress as the key actor in restructuring institutions. The study finds that the main difference lies in controlling presidential authority rather than the presidential system itself. Therefore, Indonesia needs a comprehensive legal framework for executive restructuring, clear criteria for institutional formation and evaluation, and stronger parliamentary oversight to achieve effective, accountable governance under the rule of law.